2019
DOI: 10.35940/ijitee.k2071.0981119
|View full text |Cite
|
Sign up to set email alerts
|

i- Rosa, Improved Uncertainty Aware Workflow Scheduling Algorithm

Abstract: Many applications running in cloud computing environment are workflow applications which contain large number of precedence specific tasks and so require proper schedule in order to complete successfully. Efficient scheduling of workflow applications is a challenging task. In workflows, the uncertainties like ‘uncertain data transfer time’ among dependent tasks and the uncertain task execution time, if ignored may lead to deadline violation. The proposed workflow scheduling algorithms so far unconcerned these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 14 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…One of the most notable problems with cloud computing systems, which are made up of numerous heterogeneous computing resources, is the task scheduling problem [9][10][11][12][13].…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the most notable problems with cloud computing systems, which are made up of numerous heterogeneous computing resources, is the task scheduling problem [9][10][11][12][13].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Various recent literature reviews on task scheduling in cloud computing environments can be found in [11][12][13]25,26].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation